The sword is not enough : Arabs, Israelis, and the limits of military force - Pressman, Jeremy, 1969- (Manchester University Press, 2020)
In this lucid and timely new book Jeremy Pressman demonstrates that the default use of military force on both sides of the Arab-Israeli conflict has prevented its peaceful resolution.0Whether called deterrence or war, armed struggle or terrorism, the history of the conflict reveals that violence has been counter-productive. Drawing on historical evidence from the 1950s until today, 'The sword is not enough' pushes back against the dominant belief that military force leads to triumph while negotiations and concessions lead to defeat and further unwelcome challenges. Violence weakens the security situation, bolsters adversaries, and, especially in the Palestinian case, has sabotaged political aims.0Studiously impartial and accessibly written, this book shows us that diplomacy is the only answer.